PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL KOOPERATIF TEKNIK BERTUKAR PASANGAN PADA PEMBELAJARAN IPS DI SD - Suharti, U Titin; Sabri, Tahmid; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe the enhancement Student Learning Result by using Cooperative Model techniques exchange of pairs in Social Studies learning Class V SDN 68 Pontianak Barat. The method used is a descriptive method with class action research (CAR) and is collaborative. Data collection techniques used is the direct observation and documentation techniques. The data analysis technique used is to use an average calculation formula (Mean). This research was conducted in 3 cycles with the results 1) the average ability of teachers to plan learning, namely as follows, in cycle 1 was 3.15, in cycle II was 3.70, in cycle III was 3.91. 2) the average ability of teachers to carry out learning, namely as follows, in the cycle I was 2.41, in the cycle II was 3.49, in the cycle III was 3.71. 3) the average students learning outcomes are as follows, in the cycle I was 71.18, in the cycle II was 80 and in the cycle III was 90.78. Based on the data obtained it can be concluded that by using a cooperative model techniques exchange of pairs can improve students learning outcomes. Keywords: Improvement, Cooperative Model exchange of pairs Techniques, Learning Outcomes, Social Sciences Learning